Linkage Program Bank Syariah Dengan BMT: Tinjauan Kritis Bagi Pengembangan Sistem Keuangan Islam Yang Lebih Kaffah - Denizar Abdurrahman Mi'raj; Muhammad Nafik HR (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aims to determine the BMT’s reason for not continuing linkage with Islamic Bank. Whereas linkage program is a good strategy to achieve a more inclusive financial system. This study used a qualitative approach and single-case studies as the strategy. Primary data collection using in-depth interview, while secondary data obtained from the annual financial statements of BMT. The expalanation building was used as the technique of analysis by explaining the results of in-depth interviews, in order to know what is BMT’s reason for this case.The results showed that the linkage program that used mudaraba contract which the rate of return should be variable on the income of BMT, but in fact is still based on the amount of financing. Linkage contract which is not in accordance with mudaraba system contract caused BMT did not continue linkage with Islamic banks.